2021
DOI: 10.1016/j.isci.2021.102534
|View full text |Cite
|
Sign up to set email alerts
|

ASPM promotes homologous recombination-mediated DNA repair by safeguarding BRCA1 stability

Abstract: Summary DNA double-strand break (DSB) repair by homologous recombination (HR) is essential for ensuring genome stability. Abnormal spindle-like microcephaly-associated ( ASPM ) gene encodes a spindle protein that is commonly implicated in primary microcephaly. We found that ASPM is recruited to sites of DNA damage in a PARP2-dependent manner. ASPM interacts with BRCA1 and its E3 ligase HERC2, preventing HERC2 from accessing to BRCA1 and ensuring BRCA1 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…Most of these DEGs have been reported to have potential as diagnostic and prognostic biomarkers in a specific tumor or class of tumors ( Xu et al, 2019 ; Zhao et al, 2021 ; Luo et al, 2022 ), while a few have been reported to have such potential in no less than 10 tumors ( Jiang et al, 2021 ; Pan et al, 2021 ). For example, ASPM (Assembly Factor for Spindle Microtubules) facilitates the homologous recombination-mediated repair of DNA double-strand break ( Xu et al, 2021 ), is essential for mitotic spindle function during cell replication, and plays a pivotal role in the invasiveness of bladder cancer and serves as a potential prognostic biomarker for them ( Xu et al, 2019 ). The UBE2C (Ubiquitin Conjugating Enzyme E2 C) is a conjugating enzyme, that plays a crucial role in cancer progression and its upregulation has been found in various cancers, a recent study demonstrated that overexpression of UBE2C was associated with TMB, microsatellite instability, immune cell infiltration, and diverse drug sensitivities ( Jiang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these DEGs have been reported to have potential as diagnostic and prognostic biomarkers in a specific tumor or class of tumors ( Xu et al, 2019 ; Zhao et al, 2021 ; Luo et al, 2022 ), while a few have been reported to have such potential in no less than 10 tumors ( Jiang et al, 2021 ; Pan et al, 2021 ). For example, ASPM (Assembly Factor for Spindle Microtubules) facilitates the homologous recombination-mediated repair of DNA double-strand break ( Xu et al, 2021 ), is essential for mitotic spindle function during cell replication, and plays a pivotal role in the invasiveness of bladder cancer and serves as a potential prognostic biomarker for them ( Xu et al, 2019 ). The UBE2C (Ubiquitin Conjugating Enzyme E2 C) is a conjugating enzyme, that plays a crucial role in cancer progression and its upregulation has been found in various cancers, a recent study demonstrated that overexpression of UBE2C was associated with TMB, microsatellite instability, immune cell infiltration, and diverse drug sensitivities ( Jiang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In different GBM cell lines and patient-derived GBM cells, ASPM knockdown by siRNA reduces proliferation, increases cell death, impairs DNA double-strand break repair, and enhances the sensitivity to X-rays [ 77 ]. ASPM knockdown increases chromosome aberrations in irradiated cells and inhibits homologous recombination [ 78 ] and non-homologous end joining (NHEJ) pathway in GBM [ 77 ]. Stable ASPM knockdown results in cell cycle arrest in G0/G1 phase [ 79 , 80 ].…”
Section: Microtubule Targeting Agents (Mtas) In Brain Tumorsmentioning
confidence: 99%
“…S1 ). Epithelioid CD473 cells presented a higher number of variants and some of them are known to be involved in cell proliferation and DNA damage repair ( BAP1 [ 13 ], PMS2 [ 14 ], CDK12 [ 15 ], and ASPM [ 16 ]).…”
Section: Resultsmentioning
confidence: 99%